Frequency-Domain Receiver Design for Transmission Through Multipath Channels with Strong Doppler Effects - Silva, Fábio (2015)
Single-carrier modulation (SC) with frequency-domain equalization (FDE) combined with iterative (turbo) FDE schemes has excellent performance in severely time-dispersive channels, making it a promising candidate for future broadband wireless systems. To avoid significant performance degradation due to strong Doppler effects, SC-FDE schemes employ frequency-domain receivers that require an invariant channel within the block duration. In this paper we propose iterative receivers for SC-FDE schemes able to attenuate the impact of strong Doppler effects. These receivers can be considered as modified turbo equalizers implemented in the frequency-domain, which are able to compensate the Doppler effects associated to different groups of multipath components while performing the equalization operation. The performance results show that the proposed receivers have excellent performance, even in the presence of significant Doppler spread between the different groups of multipath components. Therefore, our receivers are suitable for SC-FDE scheme based broadband transmission in the presence of fast-varying channels